Frequency and Risk Factors of Postoperative Hyponatremia in Primary Hip and Knee Arthroplasties Patients at a Tertiary Care Hospital, Karachi, Pakistan - Haider, Anam; Tareen, Hameed ullah; Syed, Furrukh Omair (Journal of Postgraduate Medical Institute, 2024)
Objective: To determine the frequency of hyponatremia and risk factors (age, comorbidities) and its impact on length of hospital stay in patients who underwent primary hip and knee replacement at a tertiary care hospital, Karachi, Pakistan. Methodology: The present study was conducted at Department of orthopedics, Agha khan hospital with cross sectional study desing, from December 10, 2019 till June 10, 2020. Sample size was 189 and these were those patients undergoing hip and knee arthroplasty. Quantitative data were presented using mean and standard deviation, while qualitative variables were described using frequencies and percentages. SPSS version 21 was utilized for data analysis. Results: The total number of study cases was 189 with mean age of 52.28±6.14 years. Out of 189 patients who underwent hip and knee arthroplasty, 84 (44.4%) had hyponatremia. Participants were divided in two Group A- who had the hyponatremia (n=84) and Group B- who had no hyponatremia (n=105). The mean± S.D of the age in both groups were 54.4±3.8 and 35.97±3.63 years (p=0.000). Participants with hyponatremia were predominantly females (73%, p=0.000). In both group participants with ASA grading 2 were abundant (67%vs56%: p=0.000). Mean± S.D of the length of stay in both groups were 6.6±1.4 and 2.85±0.94 days (p=0.000). Conclusion: Our study revealed a significant 44% incidence of postoperative hyponatremia (POH) among hip and knee arthroplasty patients. Notably, advancing age correlated strongly with POH. Additionally, prolonged surgery duration was identified as a significant risk factor.